Respons Pertumbuhan Ikan Kelabau (Osteochilus melanopleurus) Yang Diberi Pakan Menggunakan Bungkil Inti Sawit Dengan Kadar Yang Berbeda - Jordan Pratama; Mohamad Maruf; Heru Kusdianto; Adi Susanto; Komsanah Sukarti (Jurnal Akuakultur Sungai dan Danau, 2023)
Osteochilus melanopleurus (Kelabau in Indonesia) is a freshwater fish found throughout Southeast Asia, including Malaysia, Burma, and Indochina. This fish has a relatively high economic value in some locations, thus it has compelling economic motives to be cultivated. One of the most important aspects in fish farming or aquaculture activities is feed availability. Feed ingredients should have adequate nutrient content, abundantly available and inexpensive. Palm kernel meal (PKM) is one of the by-products of palm oil iondustry. Palm kernel meal contains adequate nutrients to be utilized in fish feed, in addition to being abundantly available and affordable. The purpose of this experiment was to examine the growth response of Kelabau fed various quantities of palm kernel meal (5%, 10%, 15%, and 20%). The results showed that 10% palm kernel meal inclusion produced the highest growth, daily growth rate, specific growth rate, and feed conversion ratio. However, statistical analysis showed that the addition of palm kernel meal had no effect on growth or the feed conversion ratio.